Variação da energia livre na hidratação de séries homólogas de poliol, glicina e peptídeos ANK usando modelos contínuo e discreto de solvente - Abreu, Leonardo Martins de (2017)
Using continuum and discrete solvent description models, we have investigated the chain length dependence of hydration free energy of polyol, glycine and ANK peptides. In this work this property values were calculated using thermodynamics integration with classical molecular dynamics simulation of one solute molecule to around 1000 solvent molecules. In addition, hydration free energy of polyol, glycine and ANK peptides were also calculated using polarizable continuum model in combination with the universal solvation model. Dipole moment and linear polarizability of the three systems had been also calculate using the PCM method. Our MD results show that ΔG exhibit a linear pattern with the size of glycine and ANK chain as well as observed for organic compounds in literature. In opposition, polyol’s ΔG shows a nonlinear behavior with increasing chain length and for this group of molecules it were found that water solvating effects have an important role over the polyol’s electric properties. These results suggest that in the case of polyols not only variation of polarizability but also variations of dipole moment in going from vacuum to water can influence the behavior of the free energy of hydration. All DM and PCM calculations were performed using the GROMACS 4.5 and the GAUSSIAN09 programs, respectively.